2005
DOI: 10.1111/j.1366-9516.2005.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the intermediate disturbance hypothesis: when will there be two peaks of diversity?

Abstract: Succession after disturbances generates a mosaic of patches in different successional stages. The intermediate disturbance hypothesis predicts that intermediate disturbances lead to the highest diversity of these stages on a regional scale resulting in a hump-shaped diversity-disturbance curve. We tested this prediction using field data of forest succession and hypothetical succession scenarios in combination with analytical and simulation models. According to our study the main factors shaping the diversity-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 39 publications
3
35
0
1
Order By: Relevance
“…We found that under low perturbations, the composition was determined by late-successional strategies (competitors), while under high perturbations it was determined by early successional strategies (coloniser). These outcomes are consistent with Johst and Huth (2005). Furthermore, the intensity of perturbations affects how effective less dominant, i.e.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We found that under low perturbations, the composition was determined by late-successional strategies (competitors), while under high perturbations it was determined by early successional strategies (coloniser). These outcomes are consistent with Johst and Huth (2005). Furthermore, the intensity of perturbations affects how effective less dominant, i.e.…”
Section: Discussionsupporting
confidence: 76%
“…We use a constant value for this parameter, even though many disturbances are stochastic and to some extent dependent on the climatic conditions -as is the case for fire -or on the composition of the community -as is the case for herbivory. Stochastic perturbation events have major impacts on vegetation dynamics (Johst and Huth, 2005), and different PPSs may respond differentially to perturbations. Diaz et al (2007), for instance, concluded that grazing, which expresses a form of perturbation, interacts with species composition.…”
Section: Representation Of Mortalitymentioning
confidence: 99%
“…According to the non-equilibrium disturbance paradigm, the removal of a dominant species can prevent the monopolisation of limiting resources by a small number of species (Connell & Slayter 1977, Sousa 1979, Benedetti-Cecchi & Cinelli 1992a. The intermediate disturbance hypothesis predicts that maximum diversity should occur at intermediate intensities of disturbance (Connell 1978), although these intermediate responses are known to be complex and variable (Johst & Huth 2005). Consistent with this model, highest diversity in our experiment should have occurred with a 50% reduction of canopy cover, which left some plants laying over the substratum during periods of emersion and sheltering those species in the understory, while still providing space for new species to colonise.…”
Section: Discussionmentioning
confidence: 99%
“…Besides an intensive analysis of field data now available from large long-term rain forest plots (Condit et al, 1996;Hubbell et al, 1999) quite simplistic conceptual model were used to highlight the influence of various processes and mechanisms on species abundance and diversity in the past (Connell, 1978;Sheil, 1999;Vandermeer et al, 2000;Molino and Sabatier, 2001;Roxburgh et al, 2004;Sheil and Burslem, 2003;Johst and Huth, 2005) and the concept of recruitment limitation (Hurtt and Pacala, 1995;Hubbell et al, 1999;Chazdon et al, 1999;Hubbell, 1999) acting as the main mechanisms for maintenance of tree species diversity have been discussed within recent years. Here, we attempt to add a few new aspects to the discussion regarding which mechanisms promote tropical tree species richness from a modeling perspective by using, for the first time, a complex process-based forest growth model.…”
Section: Introductionmentioning
confidence: 99%